La educación por competencias en la sociedad del conocimiento (2021)
This paper is carried out under the method of documentary research and its objective is to analyze the approach to education by competencies, under the new demands of the knowledge society. To achieve this end, the work is structured as follows: 1. It indicates the historical context in which the proposal arises. 2. Presents the theoretical foundation, which highlights the novelty and intention to respond to the demands of global society (Aldana, 2005), as well as the complex task of executing various actions to solve daily and work problems (Tobón, 2006) ). 3. Indicates the importance of adapting to the demands of the knowledge society proposed by UNESCO (2005). 4. Shows the main criticisms of the model, in which the excessive economic focus (Sánchez Parga, 2011) and the foundation in a commercial ethics (Sánchez, 2011) are distinguished. It concludes on the need to maintain a holistic approach in educational processes, without losing sight of the complexity of the human being.